Identification of GBF1 as a cellular factor required for hepatitis E virus RNA replication. (17th November 2017) - Farhat, Rayan; Ankavay, Maliki; Lebsir, Nadjet; Gouttenoire, Jérôme; Jackson, Catherine L.; Wychowski, Czeslaw; Moradpour, Darius; Dubuisson, Jean; Rouillé, Yves; Cocquerel, Laurence
Abstract: The hepatitis E virus (HEV) genome is a single‐stranded, positive‐sense RNA that encodes three proteins including the ORF1 replicase. Mechanisms of HEV replication in host cells are unclear, and only a few cellular factors involved in this step have been identified so far. Here, we used brefeldin A (BFA) that blocks the activity of the cellular Arf guanine nucleotide exchange factors GBF1, BIG1, and BIG2, which play a major role in reshuffling of cellular membranes. We showed that BFA inhibits HEV replication in a dose‐dependent manner. The use of siRNA and Golgicide A identified GBF1 as a host factor critically involved in HEV replication. Experiments using cells expressing a mutation in the catalytic domain of GBF1 and overexpression of wild type GBF1 or a BFA‐resistant GBF1 mutant rescuing HEV replication in BFA‐treated cells, confirmed that GBF1 is the only BFA‐sensitive factor required for HEV replication. We demonstrated that GBF1 is likely required for the activity of HEV replication complexes. However, GBF1 does not colocalise with the ORF1 protein, and its subcellular distribution is unmodified upon infection or overexpression of viral proteins, indicating that GBF1 is likely not recruited to replication sites. Together, our results suggest that HEV replication involves GBF1‐regulated mechanisms.